THE IMPACT OF CORPORATE GOVERNANCE ON FINANCIAL PERFORMANCE ON STATE-OWNED ENTERPRISES - Kurniawan, Timothy Brian; Viriany, Viriany (International Journal of Application on Economics and Business, 2023)
This research was conducted with the aim of determining whether corporate governance, as indicated by board size, audit committee size, the proportion of independent directors, and the proportion of independent commissioners, affects financial performance, measured by return on equity. The study was conducted on state-owned enterprises (“SOE”) listed on the Indonesia Stock Exchange from 2019 to 2022. The research used an empirical data analysis method by collecting data from the annual financial reports of publicly listed companies in Indonesia, from which 15 companies were selected. The research data was processed using multiple regression analysis with Microsoft Excel 2019 and EViews 12. The results of the study show that corporate governance significantly influences the financial performance of state-owned enterprises (SOE). Variables such as audit committee size and the proportion of independent commissioners have a positive impact on financial performance, while board size and the proportion of independent directors do not affect financial performance. The research findings emphasize the importance of implementing good corporate governance practices in state-owned enterprises. This includes having a broader audit committee and increasing the proportion of independent commissioners on the board of directors. By optimizing these aspects, state-owned enterprises can enhance their financial performance.